Immersive training in ice hockey: Evaluating the impact of virtual reality on engagement, enjoyment, and motivation - Friedrich, M. F. (International Journal of Sports Science & Coaching, 2025)
Virtual reality (VR) is emerging as a transformative tool in sports training, offering immersive environments to enhance athlete development. This study examines the potential of VR as a supplementary off-ice training method for ice hockey players, focusing on engagement, enjoyment, usability, motivation, and perceived competence. Ice hockey's fast-paced and skill-intensive nature makes innovative tools like VR valuable for addressing logistical challenges while enriching training experiences. Using a cross-over design, 33 ice hockey players participated in both VR and traditional off-ice drills, with their experiences assessed through questionnaires and statistical analysis. Results showed that VR significantly enhances engagement compared to traditional methods. However, traditional drills outperformed VR in usability and perceived competence. No significant differences were observed in enjoyment and motivation between the two modalities. These findings highlight VR's potential as a complementary training tool, particularly for boosting focus and involvement, while underscoring the need for improved usability and alignment with athletes` skill levels. By bridging psychological insights with practical applications, this study contributes to the understanding of VR in sports training and calls for longitudinal research to explore its impact on performance and skill transfer. This research addresses gaps in the application of VR in team sports, providing a foundation for advancing innovative, adaptable, and engaging training methods in ice hockey and other sports.